Benthic diatoms species richness at Dvuyakornaya Bay and other coastal sites of Crimea (the Black Sea) under various environments - NEVROVA, ELENA L.; PETROV, ALEXEI (Mediterranean Marine Science, 2019)
First-time research of the pristine water area of Dvuyakornaya Bay (South-Eastern Crimea, Black Sea) revealed high taxonomic richness of benthic diatoms (Bacillariophyta). Altogether, 304 species, 78 genera, 37 families and 20 orders were identified. Among them 68 newly-found species for the Black Sea were marked. The largest species number was marked in the genera Navicula (41 species), Nitzschia (29), Amphora (25), Cocconeis (20), Diploneis (16), Lyrella, Fallacia and Planothidium (10 species respectively). Inter-regional comparative analysis of diatom species richness was carried out using Bray-Curtis similarity coefficient and Venn diagrams. Diatom taxocene of Dvuyakornaya Bay (DB) was compared with Bacillariophyta flora from several Crimean coastal sites under different level of anthropogenic impact, i.e. relatively pristine water area near Cape Fiolent (CF) and heavy polluted Sevastopol Bay (SB) and Balaklava Bay (BB). The highest similarity of species composition (58%) was registered between intact biotopes (DB vs CF) and between heavy polluted water areas (SB vs BB), despite the geographical remoteness of the compared areas, differences in hydrological-hydrochemical conditions and in bottom substrates patterns. The lowest species similarity of diatom taxocenes was observed between SB and CF (32.3%) and between SB and DB (36.5%). It was concluded that the content of technogenic pollutants (trace metals, PCBs, PAHs and pesticides) in the bottom sediments, as well as the heterogeneity of microbiotopes are represent major factors influencing on the species composition of benthic Bacillariophyta in the investigated coastal water areas.